(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Glomerular filtration rate (GFR) is the most important and accurate measure of overall kidney functions both in good health and disease because it is the sum of the filtration rates in each of the functioning nephrons .Different GFR measuring methods have some limitations.The objective of this study was to compare the CKD-EPI formula based eGFR with that of Cock- croft- Gault formula & 4 variable MDRD formula based eGFR.This Cross-sectional analytical study was done in the Department of Biochemistry & Molecular biology, BSMMU September during the period of July 2017 to August 2018. Serum creatinine was measured and eGFR by MDRD, CKD-EPI and Cockcroft-Gault formula was calculated using the respective equations on online calculator. Comparison of eGFR values between CKD-EPI & MDRD formula and between CKD-EPI & Cockcroft-Gault formula were done among different groups. Compari- son was done by Bland Altman agreement test to see the agreement on the measurement of GFR between three equation based eGFR method. Pearson‘s correlation test revealed a positive correlation between C-G and CKD-EPI (r = 0.779), but a stronger correlation between MDRD and CKD-EPI (r = 0.934). Bland-Altman plot showed strong agreement between CKD-EPI & 4–variable MDRD than between CKD-EPI & C-G formula. From this study we may conclude CKD-EPI and MDRD formula showed better agreement than between CKD-EPI and Cockcroft-Gault formula. So, this study suggests that CKD-EPI and MDRD equations can be used to estimate GFR more effectively than Cockcroft-Gault equation in Bangladeshi population. BSMMU J 2021; 14(4): 152-156